LINGUISTIC REPRESENTATION OF NATIONAL CHARACTER IN RUSSIAN AND UZBEK PROSE - Rakhmonova Rukhsora (International Journal of Literature and Language Studies, 2026)
This article is devoted to the study of linguistic means of representing national character in Russian and Uzbek prose. It analyzes how authors of both cultures use lexical, syntactic, and stylistic devices to create images that reflect the distinctive features of their peoples. The aim of the work is to identify common and specific approaches to the formation of national types through the language of literary works. The research helps to gain a deeper understanding of the relationship between language, culture, and identity. It also reveals the specific features of the worldview characteristic of the Russian and Uzbek peoples. The obtained results contribute to broadening the understanding of cultural identity expressed in literature.